Utilizing Instagram to improve students’ recount text writing in English class - Eben Manurung; Rayendra Rayendra; Zelhendri Zen; Fetri Yeni (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aims to analyze the use of social media, particularly Instagram, in improving students’ ability to write recount texts. A quantitative experimental design was employed with 70 eleventh-grade students divided into an experimental group (Instagram-assisted instruction) and a control group (traditional instruction). Data were collected through pre- and post-tests, questionnaires, classroom observations, and document analysis to measure writing improvements in structure, vocabulary, grammar, and coherence. The findings indicate an improvement in writing skills in both groups, with a more significant increase observed in the experimental group. The average pre-test and post-test scores in the experimental class rose from 4.25 to 5.54, while the control class increased from 3.87 to 4.93. A paired sample t-test confirmed statistical significance with a Sig. value of 0.000 in both groups, underscoring the effectiveness of using social media in learning. Questionnaire results revealed that students experienced increased motivation, creativity, and confidence, while minor technical challenges were reported. Instagram proved to be an effective, interactive, and contextual learning medium.